Dominant Currencies and External Adjustment - Adler, Gustavo; Casas, Camila; Cubeddu, Luis.; Gopinath, Gita. (Washington, D.C. : International Monetary Fund, 2020)
The extensive use of the US dollar when firms set prices for international trade (dubbed dominant currency pricing) and in their funding (dominant currency financing) has come to the forefront of policy debate, raising questions about how exchange rates work and the benefits of exchange rate flexibility. This Staff Discussion Note documents these features of international trade and finance and explores their implications for how exchange rates can help external rebalancing and buffer macroeconomic shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet